The effect of low-intensity persistence exercise and high-intensity interval training on selective attention, memory, short-term and executive functions in sedentary students during the coronavirus pandemic - Mehdi Yazdanpanah; Isaac Naderyan (روانشناسی و روانپزشکی شناخت)
Introduction: Attention and memory are fundamental cognitive processes that play a crucial role in learning. The intensity of physical exercise can significantly influence cognitive functions. Aim: The present study aimed to examine the effectiveness of two types of exercise—Low-intensity persistent exercise and high-intensity interval training—on selective attention, short-term memory, and executive functions in sedentary students during the COVID-19 pandemic. Method: This study employed a quasi-experimental design with a pretest-posttest structure and a control group. The statistical population consisted of male students from Shiraz Technical and Vocational University during the 2021–2022 academic year. A total of 51 participants were selected using a convenience sampling method and were randomly assigned to two experimental groups and one control group. The experimental groups participated in an 8-week protocol of either Low-intensity persistent exercise or high-intensity interval training. Data were collected using the Stroop Color and Word test and the Wechsler Adult Intelligence Scale. Statistical analyses were conducted using analysis of covariance (ANCOVA) and Tukey's post hoc test in SPSS version 22. Results: The results indicated a significant difference between the post-test mean scores of the experimental and control groups. Specifically, low-intensity persistent exercise was found to significantly improve selective attention (F = 58.40, p = 0.001, η² = 0.89), short-term memory (F = 36.89, p = 0.003, η² = 0.75), and executive function (F = 62.66, p = 0.001, η² = 0.94) in sedentary students (p < 0.05). Conclusion: The results showed that the low-intensity persistence exercise improved selective attention, memory, short-term, and executive function in sedentary students. Accordingly, low-intensity persistence exercise was the most effective exercise in improving cognition functions as compered with high-intensity interval training.